Organic solvents-soluble zinc(II) and cadmium(II) complexes based on 2-aryl substituted-8-hydroxyquinoline: Synthesis, crystal structures, photoluminescence, thermal and theoretical studies. (15th November 2018) - Tan, Jihua; Li, Xiaoyang; Zhan, Yingying; Xiong, Jingwen; Lv, Xiaohui; Pan, Chengqiang; Huo, Yanping
Graphical abstract: Two 8-hydroxyquinoline based ligands, ( E )-2-[(4-tert-butylphenyl)ethenyl]-8-hydroxyquinoline (L1 ) and ( E )-2-[(2-chloro-3, 4-dimethoxyphenyl)ethenyl]-8-hydroxyquinoline (L2 ) as well as their zinc(II) and cadmium(II) complexes, namely Zn2 (L1 )4, Cd3 (L1 )6, Zn3 (L2 )6 and Cd3 (L2 )6 were designed and synthesized. Characterizations including X-ray crystallography, NMR spectra, UV–Vis and fluorescence spectroscopic titrations, thermogravimetric analysis as well as theoretical calculation were used to study their photophysical properties. Abstract: Two novel C-2 position modified 8-hydroxyquinoline ligands, ( E )-2-[(4-tert-butylphenyl)ethenyl]-8-hydroxyquinoline (L1 ) and ( E )-2-[(2-chloro-3, 4-dimethoxyphenyl)ethenyl]-8-hydroxyquinoline (L2 ) as well as their zinc(II) and cadmium(II) complexes, namely Zn2 (L1 )4, Cd3 (L1 )6, Zn3 (L2 )6 and Cd3 (L2 )6 were designed and synthesized. Thanks to the introduction of aromatic tert-butyl and methoxy, ligandsL1 andL2 are highly soluble and complexes are having good solubility in dimethyl sulfoxide (DMSO) and chloroform. X-ray structural analysis indicate four complexes were in P 21/ c, P 2/ c, P 1 ¯, C 2/ c space group, respectively, and exhibit a monoclinic crystal system except Zn3 (L2 )6, which hold a triclinic crystal system. Structural formulea and coordinating behavior of these complexes were also investigated by NMR, UV–Vis and fluorescence spectroscopic titrations in solution, revealing four complexes were well coordinated. Solid state photoluminescence studies reveal they emit strong yellow-orange luminescence at 568–612 nm with 5.47–11.79 ns lifetime. Thermogravimetric and theoretical electronic structure analysis indicate that four complexes appear to be promising candidates for the application as yellow luminescent materials.